Attitudes and Motives Affecting the Desire to Develop Oneself to Advance to a Higher Position of Support Personnel Uttaradit Rajabhat University - Tantuak, Phiphatphong; Yaemkong, Sirikarnda; Chomraka, Irawat (Journal of Dhamma for Life, 2025)
The purpose of this research was to study 1) factors of attitude, motive and self-development needs for advancement to higher positions, 2) factors of attitude and motive affecting self-development needs for advancement to higher positions of support personnel at Uttaradit Rajabhat University. The population used in this research was 426 support personnel. The research instrument was a questionnaire. Data were analyzed using a ready-made computer program. The statistical methods used were frequency distribution, percentage, mean, standard deviation and multiple regression. The results of the study found that the respondents Most of them were female, accounting for 55.93 percent. They were 42.80 percent aged 41-50 years. 43.20 percent had a bachelor’s degree. 42.30 percent had a work experience of 10-19 years. Their department was the division, accounting for 43.99 percent, respectively. The attitude factors affecting self-development overall were at a high level (m = 4.18, s =0.37). The motive factors affecting self-development overall were at a high level (m = 4.20, s = 0.38). The need for self-development overall was at a high level (m = 4.18, s = 0.54). All 3 attitudinal factor significantly affected the need for self-development to advance to a higher position at the 0.05 level. The multiple correlation coefficient of prediction was 22.30 percent (R2= 0.223). The 3 motive factors were policy and administration. In terms of career advancement, interpersonal relationships significantly affected the desire for self-development to advance to a higher position at a statistical level of 0.01. In terms of job success and work environment, they significantly affected the desire for self-development to advance to a higher position at a statistical level of 0.05, with a multiple correlation coefficient of 32.30 percent (R2= 0.323).